Determination of adrenal volume by MRI in healthy children: associations with age, body size, pubertal stage and serum levels of adrenal androgens. (15th February 2014) - Mouritsen, Annette; Johansen, Marie Lindhardt; Wohlfahrt‐Veje, Christine; Hagen, Casper P.; Tinggaard, Jeanette; Mieritz, Mikkel G.; Tefre de Renzy‐Martin, Katrine; Soeborg, Tue; Fallentin, Eva; Juul, Anders; Main, Katharina M.
Summary Background Adrenal disorders such as congenital adrenal hyperplasia result in abnormal adrenal size and morphology, but little is known about the clinical value of magnetic resonance imaging (MRI) in determining adrenal volume. Objective To evaluate the potential usefulness of MR methodology, to estimate adrenal size in healthy children and to evaluate determinants of adrenal volume such as age, gender, body size, pubic hair stage and serum levels of adrenal androgens. Design Two hundred and thirty‐five healthy children (116 girls and 119 boys) (age range 10·0–14·8 years) were examined by MRI. Clinical examinations (anthropometry and pubertal staging) were performed, and five androgen metabolites were measured in blood samples by liquid chromatography‐tandem mass spectrometry (LC‐MS/MS). Results It was possible to determine adrenal volume in 115/235 children using MRI. The adrenals were not measurable in 51% of children due to breathing and moving artefacts. The median volume of the right adrenal gland was 0·46 ml in girls and 0·46 ml in boys. The median volume of the left adrenal gland was 0·34 ml in girls and 0·40 ml in boys. Adrenal size was positively associated with body surface area (estimate B = 0·34 ml/year, P = 0·003), age (estimate B = 0·05 ml/year, P = 0·021) and pubic hair stage (estimate B = 0·05 ml/stage, P = 0·075). No associations between adrenal size and serum levels of adrenal androgens were observed. Conclusion It was possible to determine adrenal volume by MRI in only 50% of healthy children aged 10–15 years. Adrenal volume increased with age and Tanner stage of pubic hair. Future studies will unravel whether adrenal MRI is useful when evaluating children with adrenal diseases.